Anger: A Secularized Theological Concept. Issue 7 (3rd October 2021) - Lloyd, Vincent
ABSTRACT: Media accounts often suggest that anger motivates the rise of populist political movements. Indeed, populism and anger are so closely associated in popular discourse as to become almost one: populism just is angry people doing politics. And today, many people are angry. I class accounts of anger into two groups. Some cultural critics and philosophers take anger as a fitting response to a wrong. Others take anger, or at least a certain type of anger, as opaque, directed at the injustices baked into a normative order. By turning to accounts of anger from the Hebrew Bible, where human and divine anger is closely tied with authority, I argue that the opaque concept of anger is often forgotten, or repressed. When it is recovered, we are attuned to questions of domination, and to possibilities for flourishing in a radically different world.